1983
DOI: 10.1007/bf02029529
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of norfloxacin versus cotrimoxazole in urinary tract infections

Abstract: Forty patients with urinary tract infections were randomly assigned to receive a ten-day course of oral therapy with either norfloxacin 400 mg twice daily or cotrimoxazole (trimethoprim-sulfamethoxazole) 160/800 mg twice daily. There were 34 cases (19 in the norfloxacin and 15 in the cotrimoxazole group) of evaluable infections due to Escherichia coli (85% of cases), Klebsiella pneumoniae, Enterobacter spp., Proteus vulgaris and Alcaligenes faecalis. All organisms were sensitive to the assigned study drug. Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Cure was achieved in 91% of norfloxacin-treated patients at the 5-to 9-day posttherapy visit, and 88% continued to be asymptomatic and have negative urine cultures 4 to 6 weeks posttherapy. European studies (2,6,7,10,14) showed similar results, but several were either uncontrolled or gave sparse methodology. Clinical side effects (nausea, headache, insomnia) were seen in 23% of the SXT group and 14% of the norfloxacin group.…”
mentioning
confidence: 86%
“…Cure was achieved in 91% of norfloxacin-treated patients at the 5-to 9-day posttherapy visit, and 88% continued to be asymptomatic and have negative urine cultures 4 to 6 weeks posttherapy. European studies (2,6,7,10,14) showed similar results, but several were either uncontrolled or gave sparse methodology. Clinical side effects (nausea, headache, insomnia) were seen in 23% of the SXT group and 14% of the norfloxacin group.…”
mentioning
confidence: 86%
“…For comparative trials, treatment of acute pyelonephritis with norfloxacin as compared with TMP-SMX for 10 days eliminated pathogens from urine in 12 of 14 patients (86%) receiving norfloxacin and in 9 of 10 patients (90%) receiving TMP-SMX (30) and, in a similar study, in 10 of 11 patients (91%) receiving norfloxacin and in 5 of 5 patients receiving TMP-SMX (34) ( Table 4). For data combined from different centers, bacteriologic cure occurred in 30 of 32 patients (94%) treated with norfloxacin and in 29 of 32 patients (91%) treated with TMP-SMX (65).…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 96%
“…Mild side effects from TMP-SMX included skin rash, fever, fatigue, mild headache, vaginitis, and epigastric pain. [8][9][10]14 Serious side effects from TMP-SMX included severe headache, severe anaphylaxis reactions, and severe gastrointestinal effects. 8,10 Mild side effects from norfloxacin included fatigue, dizziness, headache, nausea, and epigastric pain.…”
Section: Study Setting and Populationmentioning
confidence: 99%
“…8,10 Mild side effects from norfloxacin included fatigue, dizziness, headache, nausea, and epigastric pain. [8][9][10] Serious side effects from norfloxacin included severe gastrointestinal effects and central nervous system effects. 8,[20][21][22] Costs.…”
Section: Study Setting and Populationmentioning
confidence: 99%